Palliative Community Health Nursing (PCHN) on Improving Family Independence in The Care of Stroke Patients - Hasanah, Uswatun; Sari HS, Senja Atika; Fitri, Nury Luthfiyatil; Ludiana, Ludiana; PH, Livana (GLOBAL HEALTH SCIENCE GROUP, 2024)
Family caregivers are important partners in the delivery of patient health care. Stroke patients need the help of family caregivers to assist in daily life. The purpose of this study was to explain the effect of PCHN development on increasing family independence in the care of stroke patients at home. The type of research is pre- experimental. The population was families of post-treatment stroke patients registered in Metro City. The sample was taken using purposive sampling technique. A total of 35 people met the inclusion criteria. The independent variable is PCHN. The dependent variable is the level of independence of the family caregiver, collected with an observation sheet of the level of independence of the family caregiver. Data were then analyzed with Wilcoxon Signed Rank Test, α ≤ 0.05. The test results showed there was a difference in the level of independence of family caregivers of stroke patients before and after PCHN (p = 0.025). PCHN can increase the independence of family caregivers in caring for stroke patients at home. Implementation of PCHN through home visits can provide information support related to stroke and home care for families. PCHN can be developed as one of the methods to improve palliative care in the community by community nurses, in order to improve the quality of life of stroke patients. Future research is expected to develop PCHN by involving a multidisciplinary team.